AIDS Malignancy Consortium 054: Safety and Immunogenicity of the Quadrivalent Vaccine in Indian Women Living With HIV. (1st June 2021) - Palefsky, Joel M.; Poongulali, Selvamuthu; Lensing, Shelly; Lee, Jeannette; Da Costa, Maria; Chein, Aung; Beulah, Faith; Murugavel, K. G.; Kumarasamy, Nagalingeswaran
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Human papillomavirus (HPV)-associated cervical cancer is a leading cause of death among Indian women. Indian women living with HIV (WLWH) may be at especially high risk. The quadrivalent HPV (qHPV) vaccine is effective in prevention of initial infection with HPV-6/11/16/18 in HIV-negative women. Little is known about previous exposure to HPV-6/11/16/18, safety, and immunogenicity of qHPV in Indian WLWH. Methodology: One hundred fifty WLWH with different CD4 levels and HIV viral load (VL) were vaccinated at 0/2/6 months at CART-CRS-IDMC, Chennai, India. Serology was performed at weeks 0, 28, and 52 for HPV-6/11/16/18 using a competitive Luminex immunoassay and for HPV-16/18 using a pseudovirion-based neutralization assay. Results: Mean age was 30.8 years (range, 19–44 years). 71/87/73/81% of women were naive (sero-negative and DNA-negative) to HPV-6/11/16/18 at baseline, respectively. Among per-protocol women naive to HPV-6/11/16/18 at baseline, 100/99/99/90%, respectively, seroconverted at week 28 and 95/96/98/71% were sero-positive at week 52, respectively. Pseudovirion-based neutralization assay identified more seroconversion to HPV-18 than competitive Luminex immunoassay. There were no significant differences in the proportion seroconverting by baseline or nadir CD4 or HIV VL; however, there was a trend for increased proportion seroconverting to HPV-18 among women with higher baseline CD4 level ( P = 0.052). There were no qHPV-related serious adverse events and no change in CD4 level or HIV VL among women on ART. Conclusions: qHPV vaccine was safe and immunogenic in Indian WLWH. A high proportion were naive to HPV-6/11/16/18 and may benefit from vaccination although many were married and several years post-initiation of sexual activity.